Relação entre precipitação pluviométrica e produtividade da cultura de soja no município de Ibirubá - RS - Silva, Robson Rigão da (2013)
The climate interferes in countless ways on human life and also in the dynamics of our planet. Nowadays it is widely accepted the conception that the climate is a condition for the distribution of human life, animals and plants, besides that, that the climate is responsible for zoning the agricultural produces and also for regulating the water cycle. Thus, this work aimed to evaluate the relation between the pluviometric precipitation and the soy production/productivity in the Brazilian middle plateau, in the city of Ibirubá RS in a case study, during a period of 31 years (between 1982 and 2012). Any man-created agricultural system depends on the climate to work, similarly to the natural ecosystem. The main climatic factors that change the agricultural production are the same elements that interfere in the natural vegetation. Among these, the solar radiation, temperature and humidity are the most important. Soy culture plays by the same rules, once it is characterized mainly by a high investment value because of the high degree of technology used in the process, what grants economic and social profitability. The specific objectives were: Evaluate the annual distribution and the relation between pluviometric precipitation and the phases of the fenologic soy cycle during the years of cultivation; Evaluate the more significant standard years, in terms of higher and lower pluviometric precipitation frequency, identified as standard-years more or less rainy and habitual that influenced the highest and the lowest soy productivity in Ibirubá, from 1982 to 2012; Identify and relate, through Climatological Hydric Balance, the influence of pluviometric precipitation variability in the final soy productivity over the most significant production-years. After the data collection and analysis, it was confirmed the hypothesis that there was a correlation between pluviometric precipitation and soy production in Ibirubá. The results were organized according to the methodology of this work, that is, based on the pluviometric precipitation criterion, which was subdivided in: pluviometric precipitation below the habitual frequency, and pluviometric precipitation above the habitual frequency. Thus, the totals of pluviometric precipitation influenced the soy production, but it was verified that the hydric distribution during the fenologic cycle, in special the periods with higher hydric demand, emergency vegetative phase (VE-Vn) and reproductive phase of grain filling (R1-R6) were fundamental for the final production. Even with the introduction of new cultivars technology, like the indeterminate growth soy types, the variability of pluviometric precipitation is still influent in the productivity.